Relativistic equation-of-motion coupled-cluster method using open-shell reference wavefunction: application to ionization potential - Pathak, H.; Sasmal, S.; Nayak, M. K.; Vaval, N.; Pal, S. (Journal of Chemical Physics, 2016)
The open-shell reference relativistic equation-of-motion coupled-cluster method within its four-component description is successfully implemented with the consideration of single- and double- excitation approximations using the Dirac-Coulomb Hamiltonian. At the first attempt, the implemented method is employed to calculate ionization potential value of heavy atomic (Ag, Cs, Au, Fr, and Lr) and molecular (HgH and PbF) systems, where the effect of relativity does really matter to obtain highly accurate results. Not only the relativistic effect but also the effect of electron correlation is crucial in these heavy atomic and molecular systems. To justify the fact, we have taken two further approximations in the four-component relativistic equation-of-motion framework to quantify how the effect of electron correlation plays a role in the calculated values at different levels of theory. All these calculated results are compared with the available experimental data as well as with other theoretically calculated values to judge the extent of accuracy obtained in our calculations.